PELAYANAN ADMINISTRASI KEPENDUDUKAN BAGI KOMUNITAS ADAT BADUY - Asnawati Asnawati (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
The research was conducted in Baduy Luar communities in the Kadu Ketug Village, Lebak Regency, Province of Banten. This study used a qualitative approach in the form of case studies. The aim of this study is describing the relationship of Baduy communities as believer of Slam Sunda Wiwitan, who hopes to get service and fulfillment of their citizenship civil rights by the government in term of the administration of residence. In particular, its should achieved through this study are (1) determining the existence of Slam Sunda Wiwitan who believed by the Baduy community; (2) determining the social relations between Baduy communities and other community outside their community; and (3) knowing the realization of their civil rights regarding the inclusion of religious identity in ID cards, birth certificate, and marriage record.